Zdolność patentowa ludzkich embrionalnych komórek macierzystych i dopuszczalność prowadzenia oraz finansowania badań nad nimi, jako przykłady niespójności dotyczącej moralnej oceny danego zjawiska, w obrębie porządku prawnego Unii Europejskiej: [The patentability of human embryonic stem cells and the acceptability of conducting and financing research on them, as examples of inconsistency, concerning the moral evaluation of a given phenomenon, within the legal order of the European Union] (Studia Prawnicze / The Legal Studies, 2012)
Zasadą obowiązującą we współczesnych porządkach prawnych państw europejskich jest swoboda prowadzenia działalności naukowej. Została ona sformułowana m.in. w Karcie Praw Podstawowych Unii Europejskiej (art. 13).Swoboda prowadzenia badań naukowych nie jest absolutna. W przypadku kolizji z innymi prawami bądź swobodami na ogół o tym, której z nich przyznać prymat, decyduje hierarchia wartości przez nie chronionych. W przypadku uznania działalności związanej z prowadzeniem badań naukowych określonego rodzaju za szkodliwą lub niepożądaną, ustawodawca może jej wprost zabronić. Może też, stosując instrumenty inne niż bezpośredni zakaz – zniechęcać do jej prowadzenia. Przykładem tego ostatniego rozwiązania jest wyłączenie dopuszczalności patentowania rozwiązań, które budzą zastrzeżenia natury moralnej. Wprowadzenie takiego zakazu nie oznacza, że opracowywanie czy eksploatacja tego rodzaju wynalazków są prawnie niedopuszczalne. Pozbawiając określone wynalazki zdolności patentowej ustawodawca potencjalnie ogranicza źródła finansowania badań prowadzących do ich powstania oraz daje wyraz swojej dezaprobacie dla otaczania ich ochroną. Human embryonic stem cell research is a very promising area of human activity, which could lead to numerous breakthroughs in medicine. It also gives rise to many controversies mainly connected, but not limited to, the problem of exploitation and possible destruction of human embryos in the process of obtaining stem cells. The stance of European Union member states on the permissibility of such research is not uniform, it can however be financed (under some restrictions) from EU funds. By financing an area of activity the EU (or in fact any other institution) endorses such activity. However, in its judgement in case C-34/10 the Court of Justice of the European Union stated essentially that the exploitation of inventions based on human embryonic stem cells would be contrary to morality and ordre public, because the development of such inventions requires prior destruction or making use of an embryo. The described situation may be an example of an axiological inconsistency within the legal system of the EU, as its institutions clearly support an activity, not merely by tolerating it, but also by assigning funds to finance it, while at this same time, this activity is being regarded as immoral or threatening to ordre public, when it comes to granting patents. This article analyses current legal situation in regard to permissibility of human embryonic stem cell research within the EU and to the patentability of human embryonic stem cells and processes of obtaining them, in order to determine whether such inconsistency actually exists and what could be the possible consequences if it does exist.